1999
DOI: 10.1136/hrt.81.6.661
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of right ventricular outflow tract obstruction with intact ventricular septum, and detection of ventriculocoronary connections

Abstract: Objectives-To determine the accuracy of prenatal diagnosis of pulmonary atresia and intact ventricular septum (PAIVS), and pulmonary stenosis, including prenatal detection of ventriculocoronary connections, to evaluate heart size during the prenatal period, and to evaluate the outcome. Design and patients-Medical records of 20 cases with prenatally diagnosed PAIVS and pulmonary stenosis were reviewed retrospectively. Prenatal and postnatal echocardiography were also reviewed and dimensions of the ventricles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 24 publications
(20 reference statements)
4
58
0
1
Order By: Relevance
“…Maeno et al reported that current high resolution ultrasound provides accurate information for prenatal diagnosis of right ventricular outflow obstruction and ventriculocoronary connection. 6 In the present study, all 18 patients had correct fetal diagnoses confirmed by postnatal echocardiography and angiographic examination. With regard to ventriculocoronary connection, we diagnosed 3 cases of right-ventricle-dependent coronary circulation.…”
Section: Prenatal Diagnosis Of Pa and Pssupporting
confidence: 51%
“…Maeno et al reported that current high resolution ultrasound provides accurate information for prenatal diagnosis of right ventricular outflow obstruction and ventriculocoronary connection. 6 In the present study, all 18 patients had correct fetal diagnoses confirmed by postnatal echocardiography and angiographic examination. With regard to ventriculocoronary connection, we diagnosed 3 cases of right-ventricle-dependent coronary circulation.…”
Section: Prenatal Diagnosis Of Pa and Pssupporting
confidence: 51%
“…In several reports, ventriculocoronary connections with PA+IVS have been demonstrated in fetal scans resulting in termination of pregnancy in half of them [12][13][14][15][16][17][18] . During the fetal period, these connections have been associated with prominent hypoplasia of the main pulmonary artery, a small tricuspid valve annulus as well as a sigmoid-shaped ductus arteriosus [16] . The extent of stenosis, interruptions or ostial atresia of the coronary arteries occurring with ventriculocoronary connections are related both to the size of the RV and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…• Development/progression of ventricular inflow, outflow and arch obstruction [53][54][55][56][98][99][100][101][102][103][104] • Development/progression of structural hypoplasia [53][54][55][56][105][106][107][108][109][110] • Development/progression of valvular regurgitation [98] • Development/progression of dysrhythmia [51,[75][76][77]98,111,112] • Development of foramen ovale restriction [66,113] • Diminution and closure of ventricular septal defect [114] • Development of ductus arteriosus aneurysm or spontaneous constriction [67,115] • Development of primary myocardial disease [31,[116][117][118][119] • Development of congestive heart failure [120][121][122][123][124] • Development of, progression or regression of cardiac tumors [125]…”
Section: Box 421 Mechanisms Of Evolution Of Fetal Heart Diseasementioning
confidence: 99%